Phytochemicals from Camellia nitidissima Chi Flowers Reduce the Pyocyanin Production and Motility of Pseudomonas aeruginosa PAO1 - Yang, Rui; Guan, Ying; Zhou, Jinwei; Sun, Bing; Wang, Zhennan; Chen, Hongjuan; He, Zhaochun; Jia, Aiqun (Frontiers in Microbiology, 2018)
Camellia nitidissima Chi, known as a medicinal and edible plant in China, exhibits multiple bioactivities, especially antibacterial activity. In this study, we investigated the inhibitory effects of the dichloromethane fraction (DF) of C. nitidissima Chi flowers on the pyocyanin production, swarming motility, and swimming motility of Pseudomonas aeruginosa PAO1, at sub-minimum inhibitory concentrations. Results showed that the DF had a remarkable inhibitory effect on pyocyanin production without influencing P. aeruginosa PAO1 growth, and concentration-dependent inhibitory effects on swarming and swimming motility. The half maximal inhibitory concentrations (IC50) were 0.158 ± 0.009, 0.139 ± 0.004, and 0.334 ± 0.049 mg/mL for pyocyanin production, swarming motility, and swimming motility, respectively. Real-time RT-PCR showed that the DF significantly down-regulated the expressions of lasR (p < 0.05) and rhlR (p < 0.01). In addition, gallic acid, catechin, ellagic acid, chlorogenic acid, quercetin, and kaempferol were identified in the DF by HPLC Triple TOF MS/MS analysis. All six identified compounds showed inhibitory effects on pyocyanin production, swarming motility, and swimming motility, though ellagic acid showed the strongest effects, with IC50 values of 0.067 ± 0.002, 0.024 ± 0.008, and 0.020 ± 0.003 mg/mL, respectively. Thus, the inhibitory effects on P. aeruginosa PAO1 virulence factors might be attributable to these six and/or other compounds in the DF of C. nitidissima Chi flowers. Consequently, the C. nitidissima Chi flower, especially the DF, might be a potential quorum sensing inhibitor of P. aeruginosa PAO1.